The Effects of Water Activity and Enzyme Modification on Lipase Activity During Esterification - Taib, Mariam (1999)
Lipase from Candida rugosa was modified and the water activity (3w) required by the enzyme, in order to be optimally active, was investigated. Two methods of modification were used, which were reductive alkylation and modification with polyethylene glycols. For the first method, three types of aldehydes were studied - propionaldehyde, octyldehyde and dodecyldehyde. Two PEGs were used - PEG 2000 and PEG5000, for the second method. On the effect of 3w on different degree of modified-lipases, the optimum 3w for propyl-lipase decreased with increasing degree of modification. As for octyl-lipase, the optimum 3w also decreased with increasing degree of modification, up to 60% modification. Further modification will increase the optimum 3w of the octy l-lipase. The a.v for dodecyl-lipase, on the other hand, increased with increasing degree of modification. A similar trend was also observed with PEG -lipases, up to a certain degree of modification. It was found that the optimum a.v of the enzymes, depended on the degree of modification, hydrophobicity and also the chain-length of the modifier. The relative activity increased with increasing degree of modification for all modified enzymes tested except for dodecyl-lipase, where the activity decreased as the degree of modification increased. On the effects of solvent on the 3w of the propyl-lipase, there is no significant difference of optimum 3w requirement in the solvents tested, compared to native lipase. The optimum 3w of octyl-lipase generally shifted to a lower value in hydrophobic solvents, while for dodecyl-lipase, the optimum 3w shifted to higher values. In all solvents tested, the optimum 3w of PL2 000 are different, while PL5 000 required higher 3w, In general, the relative activity of the modified enzymes are better in non -polar solvents, compared to polar solvents.